Circular Economy Role in Industry and Environmental Sustainability: Qualitative Content Analysis Approach - Sri Harnani; Suryaning Bawono; Mirta Wahyu Wulandari (Asia Pacific Journal of Management and Education (APJME), 2022)
Our research employs the qualitative research approach, and the outcome of our investigation is a hypothesis based on the findings of prior studies. We conducted an analysis starting from the influence of forests on various sectors and their interrelationships. We will investigate forest research systems and the principle of the circular economy. Naturally, forests and the circular economy are closely associated with industrial expansion. We identified four main topics in our initial research to understand the future potential benefits of a circular economy: Forests, Industry and Environmental Sustainability, Circular Economy, and pollution. Each subject is developable based on our study of thousands of research articles discovered using direct scientific search, emerald, and Google Scholar. Forests play a role as a supporter and an indicator of the success of sustainable economic development in industrial revolution 4 and circular economics. Industry and environmental sustainability are at the center of the concept of circular economics. Circular financial play a significant role in addressing ecological improvements—pollution results from industrial activities that threaten the environment and must be recycled or minimized.